The small production and the recent situation of Brazilian agriculture - Leite, Sérgio Pereira (Universidade Estadual Paulista / UNESP, 2009)
The purpose of this paper is to analyse the family farm production. This analysis is fundamented on the Wanderiey, Martins and Silva's works. The production and reproduction of the social relationship is important to look your "spaces" (or "places") in the capitalism development.